The binding of doxepin to histamine H1-receptors in guinea-pig and rat brain. - Aceves, J. (Nature Publishing Group, 1985)
The affinity constant for doxepin obtained from inhibition of histamine-induced contraction of guinea-pig intestinal smooth muscle at 30 degrees C was 2.6 +/- 0.18 X 10(10)M-1. The slope of a Schild plot was not significantly different from unity. The affinity constant of doxepin did not vary markedly with temperature. At 37 degrees C it was 3.75 +/- 0.02 X 10(10)M-1 and at 25 degrees C 2.1 X 10(10)M-1. Doxepin was a competitive inhibitor of [3H]-mepyramine binding to guinea-pig cerebellar homogenates. The affinity constant derived for doxepin at 30 degrees C was 1.12 +/- 0.45 X 10(10)M-1. Hill coefficients for curves of doxepin or mepyramine inhibition of [3H]-mepyramine binding in guinea-pig cerebellum, cerebral cortex and hippocampus did not differ significantly from unity. The mean affinity of mepyramine for histamine H1-receptors in rat brain homogenates at 30 degrees C was 3.5 X 10(8)M-1. Hill coefficients for curves of doxepin or mepyramine inhibition of [3H]-mepyramine binding to homogenates of rat cerebral cortex or rat whole brain were near unity. These studies provide no evidence that doxepin binds preferentially to a sub-class of histamine H1-receptors in rat brain.